Electron microscopic investigations on the postnatal development of thymus in the guinea pig - Karan, M; Dinc, G (Indian Veterinary Journal, 2006)
[Abstract Not Available]
Keywords: Epithelial-Cells; Rat Thymus; Ultrastructure